Handbook of environmental and resource economics - Van den Bergh Jeroen (Cheltenham, UK: Edward Elgar, 1999)
The aim of this handbook is to bring together in a systematic structure advanced but accessible surveys of a wide range of topics in 'environmental and resource economics' (E&RE).
Includes bibliographical references and index
osc 06/09/2016, ijb 09/04/2019
Loans
Keywords: Environmental Economics; Environmental policy; Natural resources; Economics